EFFECT OF LEADERSHIP, CUSTOMER FOCUS, EMPLOYEE TRAINING AND EMPOWERMENT, PROCESS MANAGEMENT, AND CONTINUOUS IMPROVEMENT ON OPERATIONAL PERFORMANCE (CASE STUDY AT PLASTIC INJECTION COMPANY FOR AUTOMOTIVE AND ELECTRONIC COMPONENTS IN NORTH JAKARTA) - R. Moh. Arief Budihartono; Aloysius Harry Mukti; Suryati Veronika (JURNAL ILMIAH BISNIS, PASAR MODAL DAN UMKM, 2022)
This research was conducted to test and analyze the effect of leadership, customer focus, employee training and empowerment, process management, and continuous improvement as elements of Total Quality Management on operational performance. The method used in this study is Structural Equation Modeling (SEM) using the SmartPLS application. The population in this study is the employee of The Plastic Injection Company for automotive and electronic components in North Jakarta (the “Company”) as many as 450 people. The type of sample in this study was purposive sampling and obtained by respondents as many as 206 respondents. The test results showed that leadership negatively affects operational performance, customer focus has no effect on operational performance, employee training and empowerment have no effect on operational performance, process management has a positive effect on operational performance, and continuous improvement has a positive effect on operational performance